2006
DOI: 10.1038/sj.gt.3302794
|View full text |Cite
|
Sign up to set email alerts
|

A guanylate kinase/HSV-1 thymidine kinase fusion protein enhances prodrug-mediated cell killing

Abstract: Herpes simplex virus thymidine kinase (HSVTK) with the guanosine analog ganciclovir (GCV) is currently the most widely used suicide gene/prodrug system for gene therapy of cancer. Despite the broad application of the HSVTK/GCV approach, phosphorylation of GCV to its active state is inefficient such that high, myelosuppressive doses of GCV are needed to observe an antitumor effect. One strategy used to overcome the poor substrate specificity of HSVTK towards GCV (K m ¼ 45 mM) has been to create novel forms of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…The most extensively evaluated of these is mutant SR39, which is 43-fold more sensitive to GCV and 20-fold more sensitive to ACV than the parental HSVtk (Black et al, 1996(Black et al, , 2001. Applying a completely different strategy to improve the therapeutic effect of the HSVtk/GCV system, Willmon et al succeeded in decreasing the IC 50 of GCV by 175-fold by using a fusion protein of HSVtk and guanylate kinase (GMK), the cellular enzyme converting GCV-DP to GCV-TP following phosphorylation of GCV by HSVtk, when compared to HSVtk alone (Willmon et al, 2006).…”
Section: Thymidine Kinasementioning
confidence: 97%
“…The most extensively evaluated of these is mutant SR39, which is 43-fold more sensitive to GCV and 20-fold more sensitive to ACV than the parental HSVtk (Black et al, 1996(Black et al, , 2001. Applying a completely different strategy to improve the therapeutic effect of the HSVtk/GCV system, Willmon et al succeeded in decreasing the IC 50 of GCV by 175-fold by using a fusion protein of HSVtk and guanylate kinase (GMK), the cellular enzyme converting GCV-DP to GCV-TP following phosphorylation of GCV by HSVtk, when compared to HSVtk alone (Willmon et al, 2006).…”
Section: Thymidine Kinasementioning
confidence: 97%
“…In particular, poor prodrug activation kinetics, 15,16 limited cell toxicity mechanisms, 17 evolution of drug resistance, 18,19 and prophylactic use of GCV in the clinic 20 impact broad implementation of that approach. Furthermore, the poor lipophilicity of the hydrophilic GCV and its reduced ability to penetrate the blood --brain barrier are considered limiting in HSV-tk/GCV-based applications targeted to the brain in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…While BmGK K m for dGMP was found to be similar to humans (Auvynet et al 2009), differences were found with K m of GMP as compared with humans, mouse, yeast, P. falciparum and Arabidopsis thaliana (Li et al 1996;Kumar et al 2001;Willmon et al 2006;Kandeel et al 2008;Auvynet et al 2009). Lower K m value for GMP as compared with the human enzyme indicates a higher affinity for GMP and thus a tendency to convert substrate into product at a higher rate.…”
Section: Discussionmentioning
confidence: 87%